Product selective reaction controlled by the combination of palladium nanoparticles, continuous microwave irradiation, and a co-existing solid; ligand-free Buchwald–Hartwig amination vs. aryne amination. Issue 20 (28th September 2021) - Yamada, Makito; Ohta, Ryousuke; Harada, Kazuo; Takehara, Tsunayoshi; Haneoka, Hitoshi; Murakami, Yosuke; Suzuki, Takeyuki; Ohki, Yuuta; Takahashi, Naoyuki; Akiyama, Toshiki; Sirimangkalakitti, Natchanun; Sako, Makoto; et al.
Abstract : We have developed a continuous microwave irradiation-assisted Buchwald–Hartwig amination using our original Pd nanoparticle catalyst with a copper plate as a co-existing metal solid. Abstract : We have developed a continuous microwave irradiation-assisted Buchwald–Hartwig amination using our original Pd nanoparticle catalyst with a copper plate as a co-existing metal solid. In this methodology, a microwave-controlled product selectivity was achieved between Buchwald–Hartwig amination and aryne amination performed under strongly basic conditions and at a high reaction temperature, because a polar chemical species such as Ar–Pd–halogen might be activated selectively by microwave radiation. Moreover, our catalyst could be used repeatedly over 10 times, and the amount of Pd leaching could be suppressed to a low level.